Bidirectional Transmission in an Optical Network on Chip With Bus and Ring Topologies - S. Faralli; F. Gambini; P. Pintus; M. Scaffardi; O. Liboiron-Ladouceur; Y. Xiong; P. Castoldi; F. Di Pasquale; N. Andriolli; I. Cerutti (IEEE Photonics Journal, 2016)
In photonic integrated networks on chip (NoCs), microrings are commonly used for adding or dropping a single optical signal to be switched in the NoC. This paper demonstrates the feasibility of adding or dropping two optical signals at the same wavelength in the same microring of NoCs with bus and ring topology. More specifically, the same microring can be used to support simultaneous bidirectional transmissions of two signals to be coupled in the NoC topology, leading to two different configurations, called shared source-microring and shared destination-microring. Spectral characterization shows good agreement between simulations and measurements taken on silicon-based integrated NoC. Bit-error-rate (BER) measurements indicate that the shared source-microring configuration performs better, achieving a penalty as low as 1.5 dB for a BER of $10^{-9}$ at 10 Gb/s in the bus NoC. A higher penalty in the ring NoC for both configurations is due to higher crosstalk in the interconnecting ring.